2021
DOI: 10.3390/ijms22063016
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin and Its Binding Proteins in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder that manifests with rest tremor, muscle rigidity and movement disturbances. At the microscopic level it is characterized by formation of specific intraneuronal inclusions, called Lewy bodies (LBs), and by a progressive loss of dopaminergic neurons in the striatum and substantia nigra. All living cells, among them neurons, rely on Ca2+ as a universal carrier of extracellular and intracellular signals that can initiate and control various cellular processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…Aβ, tau, and α-synuclein are all found in Lewy bodies in both PD and LBD [ 36 , 37 ]. A recent review of CaMBPs in PD focused on experimentally validated CaMBPs, including CaMKII, calcineurin, NMDAR, AchR, Adenosine A2AR, and cdk5, but failed to mention or assess the CaM-binding ability of other critical PD proteins, including the risks and biomarkers covered here [ 38 ]. The involvement of CaMKII and A2AR in psychiatric disorders was discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ, tau, and α-synuclein are all found in Lewy bodies in both PD and LBD [ 36 , 37 ]. A recent review of CaMBPs in PD focused on experimentally validated CaMBPs, including CaMKII, calcineurin, NMDAR, AchR, Adenosine A2AR, and cdk5, but failed to mention or assess the CaM-binding ability of other critical PD proteins, including the risks and biomarkers covered here [ 38 ]. The involvement of CaMKII and A2AR in psychiatric disorders was discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Calmodulin, a regulator of several pathways related to cell proliferation and survival, 94,95 displayed excellent diagnostic accuracy, and its potential use in the clinical setting deserves careful assessment. In fact, although cell cycle dysfunction has been previously associated with neurodegenerative disorders, 96 deregulation of calmodulin levels can be associated with other non-neurodegenerative diseases, like cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that 91 target genes were enriched only in the calcium signaling pathway ( Figures 3E , F ). Calcium signaling pathways play an important role in PD (Calì et al, 2014 ; Bohush et al, 2021 ). Therefore, our study may contribute to understanding the molecular mechanisms underlying PD.…”
Section: Discussionmentioning
confidence: 99%